2002
DOI: 10.1046/j.1420-9101.2002.00429.x
|View full text |Cite
|
Sign up to set email alerts
|

Phylogeographical patterns in chloroplast DNA variation within the Acacia acuminata (Leguminosae: Mimosoideae) complex in Western Australia

Abstract: The Acacia acuminata complex includes three taxa, A. acuminata ssp. acuminata, A. acuminata ssp. burkittii and A. oldfieldii, along with several informal variants of A. acuminata. It is widespread throughout southern Australia with the centre of diversity in south-west Western Australia. Phylogeographical patterns in the complex were investigated using a nested clade analysis of cpDNA RFLPs from 25 populations in Western Australia. Except for A. oldfieldii that was clearly identified as a distinct entity, hapl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
59
0

Year Published

2003
2003
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 69 publications
(63 citation statements)
references
References 58 publications
4
59
0
Order By: Relevance
“…The identification of similar phylogeographic patterns over similar time frames suggests that they have occurred through the influences of broad biogeographic processes. The isolation and differentiation of lineages observed within S. spicatum, and other species that have been investigated (Byrne et al, 1999(Byrne et al, , 2001b(Byrne et al, , 2002, is consistent with the hypothesis that cyclic contraction and expansion of the arid region in the northeast, and the mesic region in the south-west, during the Pleistocene era led to fragmentation and isolation in the intermediate area between the arid and mesic zones (Hopper, 1979;Hopper et al, 1996). Comparative phylogeographic studies in other parts of the world have also demonstrated broad biogeographic influences, including common postglacial colonisation routes in Europe (Ferris et al, 1993Demesure et al, 1996;Dumolin-Lapègue et al, 1997;King and Ferris, 1998) and northern and southern glacial refugia in the Pacific North West of America (Soltis et al, 1997).…”
Section: Discussionsupporting
confidence: 67%
See 4 more Smart Citations
“…The identification of similar phylogeographic patterns over similar time frames suggests that they have occurred through the influences of broad biogeographic processes. The isolation and differentiation of lineages observed within S. spicatum, and other species that have been investigated (Byrne et al, 1999(Byrne et al, , 2001b(Byrne et al, , 2002, is consistent with the hypothesis that cyclic contraction and expansion of the arid region in the northeast, and the mesic region in the south-west, during the Pleistocene era led to fragmentation and isolation in the intermediate area between the arid and mesic zones (Hopper, 1979;Hopper et al, 1996). Comparative phylogeographic studies in other parts of the world have also demonstrated broad biogeographic influences, including common postglacial colonisation routes in Europe (Ferris et al, 1993Demesure et al, 1996;Dumolin-Lapègue et al, 1997;King and Ferris, 1998) and northern and southern glacial refugia in the Pacific North West of America (Soltis et al, 1997).…”
Section: Discussionsupporting
confidence: 67%
“…Using this estimate, the time of divergence between the two lineages is around one million years ago, in the middle of the Pleistocene era. Geographical structuring due to historical isolation has also been observed in a common host of S. spicatum, A. acuminata (Byrne et al, 2002) with a similar time frame for the divergence between lineages (approximately 800 000 years BP). The identification of similar phylogeographic patterns over similar time frames suggests that they have occurred through the influences of broad biogeographic processes.…”
Section: Discussionmentioning
confidence: 77%
See 3 more Smart Citations